2019
DOI: 10.5115/acb.19.141
|View full text |Cite
|
Sign up to set email alerts
|

Platycarya strobilacea leaf extract protects mice brain with focal cerebral ischemia by antioxidative property

Abstract: The leaf extract of Platycarya strobilacea (PSL) has long been recognized as possessing various health-promoting activities. However, information on its possible protective effects against ischemic stroke is currently lacking. Here, using a mouse model of focal cerebral ischemia (fCI), we studied the protective potential of an oral supplement of PSL. Mice were randomly divided into four groups: SO, a group subjected to a sham-operation; VEH, pretreated with distilled water and subjected to middle cerebral arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…ROS generation is implicated in the I/R injury, increased ROS could lead to neuronal cell death. 16 , 20 In addition, oxidative damage can consume intracellular antioxidants (GSH and SOD), and lead to the production of MDA. 21 , 22 Evidences have shown that cerebral I/R injury could increase ROS generation and induce oxidative stress by suppressing the activities of antioxidant biomarkers, 23 , 24 which were again confirmed in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ROS generation is implicated in the I/R injury, increased ROS could lead to neuronal cell death. 16 , 20 In addition, oxidative damage can consume intracellular antioxidants (GSH and SOD), and lead to the production of MDA. 21 , 22 Evidences have shown that cerebral I/R injury could increase ROS generation and induce oxidative stress by suppressing the activities of antioxidant biomarkers, 23 , 24 which were again confirmed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…SD rats (8 weeks old) were obtained from Shanghai SLAC Animal Center. Middle cerebral artery occlusion (MCAO) was performed in accordance with methods described by Lee et al 16 Briefly, rats were anaesthetized with ketamine (30 mg/kg) and xylazine cocktail (20 mg/kg). After that, a 7–0 surgical nylon monofilament with a rounded tip was inserted into the internal carotid artery (ICA), then occluding the middle cerebral artery (MCA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of MCAO/R was conducted under isoflurane anesthesia (2% induction, 1.5% maintenance), following a previous established protocol [35]. A midline neck incision was made, and the left common carotid artery (CCA) and the external carotid artery were tied off.…”
Section: Mcao/rmentioning
confidence: 99%
“…In accordance with our previous research [35], we employed neurological deficit scoring (NDS) as the initial assessment for sensorimotor deficits. Briefly, at 24 h after MCAO/R, we evaluated the sensorimotor functions of mice (n = 10 per group) using a scoring scale with four categories: 0 for no neurological deficit, 1 for failure to spread out the affected forepaw, 2 for unidirectional circling, 3 for falling to one side, and 4 for no voluntary movement.…”
Section: Neurological Deficit Scoringmentioning
confidence: 99%